Planting and Sowing Seeds of Hope: A Case Study on the Resonance of Tagline to Learners - Tiburcio, Jennifer M.; Lariosa, Camille Z.; Nacua, Jonathan P. (Future Science / FSH-PH Publications, 2021)
This research aimed to identify the resonance of the tagline on the students of Ignacio B. Villamor Senior High School. The researchers utilized the case study as the method of the study. The participants of the study are students-at-risk of dropping out, SSG students, and honor students in second quarter of S.Y. 2020-2021. There are 108 students who became the participants of the study. To gather data, the researchers used purposive sampling in the study. It is a non-probability sampling. The researcher identified common codes, categories, and themes. Aside from these, the researchers included statements of the participants of the study; but, their names are not identified to maintain confidentiality. The researchers proposed an organizational action plan based on themes emerged from the study.